Sistem Pemantauan Pasien berbasis IoT menggunakan ESP8266 dan Arduino - Stefanus Adi Putra Pratama; Djoni Haryadi Setiabudi (Jurnal Infra, 2020)
Health monitoring is a major problem in the world today. Due to lack of proper health monitoring, patients can suffer serious health problems. There are many devices today to monitor the health of patients that health experts use to monitor their patients but because it is not integrated with IoT, this method can add to the burden of medical personnel to conduct examinations and cannot be done anytime, anywhere. This research was conducted to make it easier for a doctor and a relative of a person with heart problems to conduct surveillance in Real Time. The Arduino device will read each sensor and by using services from ThingSpeak and IFTTT, data readings can be received and visualized, then automatically recorded on Google Sheets so that they can be accessed either via the internet or mobile applications. The combination of IoT and Arduino is one way to introduce the IoT method. By utilizing IoT, monitoring can be made easier because it is not limited in space, real-time delivery of information also facilitates decision making in the event of a critical situation.